Preliminary analysis of the diagnostic value and mechanism of action of TGFbI and S100A4 in hepatocellular carcinoma - Zhao, Liang; Shu, Qinghua; Sha, Bowen; Wu, Miao; Zhang, Yufeng (Journal of Medical Biochemistry, 2025)
Background: To analyze the diagnostic value of transforming growth factor-beta-induced protein (TGFβI) and S100 calcium-binding protein A4 (S100A4) on hepatocellular carcinoma (HCC), and to further explored the effects of TGFβI and S100A4 on ferroptosis in HCC cells. Methods: We retrospectively analyzed 76 patients with HCC admitted to our hospital from October 2022 to June 2023, and detected the differences in the expression of TGFβI and S100A4 in cancerous tissues and paracancerous tissues to analyze their diagnostic and prognostic assessment value for HCC. Additionally, the HCC cell line HepG2 was purchased and transfected with TGFβI and S100A4 abnormal expression plasmids to check changes in cell viability, oxidative stress damage, mitochondrial damage, and ferroptosis. Results: TGFβI and S100A4 were upregulated in HCC tissues (P
Keywords: TGFβI; S100A4; Hepatocellular carcinoma; Ferroptosis; Diagnostic